A Contemporary Bi-Face Dc to Dc Converter for Zero Voltage Switching - Susila, M.; Karthik, B.; Virgin, G. Angelo (International Journal of Psychosocial Rehabilitation, 2018)
A novel bi-face DC-DC converter for zero voltage switching has been presented in this paper. This design has a good isolation, efficiency and power density compared to existing bi-face DC-DC converter (BDC) modules. The reliability and low weight power converters are of high need to achieve this demand our proposed system has necessary capabilities. To describe this we have simulated a 348 V to 48 V and 48 V to 348 V BDC. The maximum power supplied to the components is 1.65 kW for both the proposed system and to the currently available system. The proposed system provides good efficiency numbers of +1.5% increase at 100% load, a +3.4% increase at 50% load and a +13.5% increase in efficiency at 10% load in both forward and backward mode and more than double power density.